العوامل التي يمكن أن تؤثر على سلوك الامتثال الضريبي في سورية أنموذج مقترح - الضابط, مدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This paper aimed to study the factors that may affect tax compliance in Syria through a comprehensive review of the literature and previous studies in this field, and try to draw a model for this compliance commensurate with the Syrian environment. For research purposes, reliance was placed on previous studies in Syria that could be used at this level, and on research tools such as personal interviews, which included many tax administration personnel and taxpayers alike. The results of this research have shown the possibility of drawing up a model that includes all the factors that can affect the tax compliance, both economic and non-economic, and commensurate with the Syrian environment. Which, if applied later, explains the behavior of tax non-compliance by taxpayers, the loss of trust between them and the tax administration, and hence the high rate of tax evasion, especially in terms of income taxes. The paper recommends that this model be applied in subsequent studies to determine the potential impact of each of these factors. The tax administration in Syria can benefit from this study and subsequent studies that can measure these effects, especially in the absence of a program to measure the compliance of the taxpayers annually with the same as in many other tax systems. هدف هذا البحث إلى دراسة العوامل التي يمكن أن تؤثر على الامتثال الضريبي في سورية. وذلك من خلال مراجعة شاملة للأدبيات والدراسات السابقة في هذا المجال، ومحاولة استخلاص أنموذج لهذا الامتثال يتناسب مع البيئة السورية. ولأغراض البحث، تم الاعتماد على الدراسات السابقة في سورية التي يمكن الاستفادة منها على هذا المستوى، وعلى أدوات بحثية كالمقابلات الشخصية، والتي شملت العديد من العاملين في الإدارة الضريبية، والمكلفين بالضريبة على حد سواء. وقد أظهرت نتائج هذا البحث إمكانية استخلاص أنموذج يشتمل على جميع العوامل التي يمكن أن تؤثر على الامتثال الضريبي سواء الاقتصادية منها وغير الاقتصادية، وبما يتناسب مع البيئة السورية. والذي يفسر على نحو هام، في حال تطبيقه لاحقاً، سلوك عدم الامتثال الضريبي من قبل المكلفين، وفقدان الثقة بينهم وبين الإدارة الضريبية، وبالتالي معدل التهرب الضريبي المرتفع وخاصة لجهة الضرائب على الدخل. يوصي الباحث بتطبيق هذا الأنموذج في دراسات لاحقة، لمعرفة مدى التأثير المحتمل لكل عامل من تلك العوامل. كما يمكن أن تستفيد الإدارة الضريبية في سورية من هذه الدراسة والدراسات اللاحقة التي يمكن أن تتولى قياس هذه الآثار، خاصة في ظل غياب برنامج لقياس مدى امتثال المكلفين سنوياً لديها أسوة بالعديد من الأنظمة الضريبية الأخرى.